PENERAPAN MODEL PEMBELAJARAN PETA PIKIRAN UNTUK MENINGKATKAN BERPIKIR KRITIS DAN KETERAMPILAN MENULIS KARANGAN NARASI - Nurhayati Nurhayati (UNIB Press, 2022)
This study aims to describe the application of the mind map learning model in improving students' critical thinking, improving the writing skills of narrative essays in Indonesian students of grade VII SMPN 3 Kikim Timur, describing how the effectiveness of the application of the mind map learning model in improving the writing skills of narrative essays in the eyes. Indonesian language lessons. The research design used was classroom action research (PTK) and quasi-experimental. The research subjects were students of class VII.A for the PTK class, class VII.B students for the experimental class and class VII.C students for the control class even semester of the 2020/2021 school year. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. The results of the study concluded that the mind map learning model could improve students' critical thinking and narrative essay writing skills in Indonesian class VII SMPN 3 Kikim Timur subjects